A Review of Adrenomedullin in Pediatric Patients: A Useful Biomarker - Anna Solé-Ribalta; Sara Bobillo-Pérez; Iolanda Jordan-García (MDPI AG, 2022)
Adrenomedullin has several properties. It acts as a potent vasodilator, has natriuretic effects, and reduces endothelial permeability. It also plays a role in initiating the early hyperdynamic phase of sepsis. Since its discovery, many articles have been published studying the uses and benefits of this biomarker. The aim of this review is to determine the usefulness of adrenomedullin in pediatric patients. Relevant studies covering adrenomedullin in pediatrics (<18 years) and published up until August 2021 were identified through a search of MEDLINE, PubMed, Embase, Web of Science, Scopus, and Cochrane. Seventy studies were included in the present review, most of them with a low level of evidence (IV to VI). Research on adrenomedullin has primarily been related to infection and the cardiovascular field. The performance of adrenomedullin to quantify infection in children seems satisfactory, especially in sepsis. In congenital heart disease, this biomarker seems to be a useful indicator before, during, and after cardiopulmonary bypass. Adrenomedullin seems to be useful in the pediatric population for a large variety of pathologies, especially regarding infection and cardiovascular conditions. However, it should be used in combination with other biomarkers and clinical or analytical variables, rather than as a single tool.